2018
DOI: 10.1007/s00467-018-3940-4
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia reperfusion injury: mechanisms of progression to chronic graft dysfunction

Abstract: The increasing use of extended criteria organs to meet the demand for kidney transplantation raises an important question of how the severity of early ischaemic injury influences long-term outcomes. Significant acute ischaemic kidney injury is associated with delayed graft function, increased immune-associated events and, ultimately, earlier deterioration of graft function. A comprehensive understanding of immediate molecular events that ensue post-ischaemia and their potential long-term consequences are key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 116 publications
(130 reference statements)
0
18
0
1
Order By: Relevance
“…According to experimental studies, targeting inflammatory pathways has a protective action in rodents; conversely, clinical studies have shown that targeting the same pathways in humans has no therapeutic effect. Moreover, bridging the underlying mechanisms of acute rejection and ischemic graft injury with intervention with novel therapeutic agents would be of paramount importance (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…According to experimental studies, targeting inflammatory pathways has a protective action in rodents; conversely, clinical studies have shown that targeting the same pathways in humans has no therapeutic effect. Moreover, bridging the underlying mechanisms of acute rejection and ischemic graft injury with intervention with novel therapeutic agents would be of paramount importance (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Renal IRI, which contributes greatly to AKI, is one of the most critical issues for many clinical situations, including renal transplantation, nephrectomy, sepsis, and repair of suprarenal aneurism [ 129 131 ]. Hu et al [ 132 ] used a microarray assay to find that 2218 genes are differentially expressed in renal IRI, including 1103 upregulated genes and 1115 downregulated genes.…”
Section: Lncrna/circrna-mirna-mrna Axis In Irimentioning
confidence: 99%
“…IRI is one of the most important but unavoidable risk factors for causing the impairment of graft function. Renal IRI triggers the generation of reactivate oxygen species, causing oxidative injury, acute inflammation and eventually necrosis, and apoptosis of renal tubular epithelial cells (Gu et al , 2018 ; Situmorang and Sheerin, 2018 ). These responses can evoke the anti-inflammatory and repair processes to initiate the recovery of the graft function (Sanchez-Nino et al , 2016 ; Pressly and Park, 2017 ).…”
Section: Introductionmentioning
confidence: 99%